The protein modifier SUMO is critical for integrity of the Arabidopsis shoot apex at warm ambient temperatures. (9th June 2021) - Hammoudi, Valentin; Beerens, Bas; Jonker, Martijs J; Helderman, Tieme A; Vlachakis, Georgios; Giesbers, Marcel; Kwaaitaal, Mark; van den Burg, Harrold A
Abstract : The protein modifier SUMO is needed for sustained rosette development when Arabidopsis endures a non-detrimental warm period of 28 °C. Abstract: SUMO is a protein modification whose conjugate levels peak during acute heat stress. Here, we found that SUMO is also critical for plant longevity when Arabidopsis experiences a prolonged non-damaging period of 28 °C. Thermo-lethality at 28 °C was seen in sumo1/2 knockdown mutants but not in any other mutant of the SUMO pathway tested. Autoimmunity due to low SUMO1/2 expression levels was not causal for this thermo-lethality. The role of SUMO in thermo-resilience was also distinct from its requirement for thermomorphogenesis—a growth response triggered by the same warm temperature, as only the latter response was also dependent on the SUMO ligase SIZ1. Thermo-resilience at 28 °C and (acquired) thermotolerance, a response that allows plants to recover and acclimate to brief extreme temperatures, both depend on the HEAT SHOCK TRANSCRIPTION FACTOR A1 (HSFA1). Acquired thermotolerance was, however, normal in the sumo1/2 knockdown mutant. Thus, SUMO-dependent thermo-resilience is potentially controlled in a different way from the protein damage pathway that underpins thermotolerance. Close inspection of shoot apices revealed that the cell patterning and tissue integrity of the shoot apex of the SUMO1/2 knockdown mutant was lost at 28 °C but not 22 °C. We thus describe a novel SUMO-dependent phenotype.